Impact of Traumatic Sports Injury on an Athlete’s Psychological Wellbeing, Adherence to Sport and Athletic Identity - Dacus, Laurel; Castagno, Christopher; Castagno, Ciara; Gontre, Gil; Weiss, William M (Journal of Sports Medicine and Therapy, 2023)
Introduction: Sports injuries can affect athletes across all ages, sexes, and levels of competition. The mental aspect of acute sports injury is often overlooked by coaches, trainers, and medical professionals. This study investigated if and how an acute traumatic sports injury affects an athlete’s psychological well-being, adherence to sport, and athletic identity. Methods: The study consisted of surveys sent to former or current athletes over 18 with one or more athletic injuries. The Qualtrics surveys were anonymous, and participants consented to the study within the survey. Results: There were 101 total participants (20.2% response rate) with an average age of 36. All reported one or more acute athletic injuries throughout their athletic careers. Specific survey sets were compared against each other using a variable correlation analysis (p - value < 0.05) and via Pearson’s Correlation. Conclusion: The results indicated that injury impacts the lives of athletes most significantly on the field and can harm their performance based on their perception of the severity of the injury. However, this decline in performance and decrease in confidence does not correlate to an athlete’s desire to leave their sport or how they identify as being an athlete. Takeaways: 1) The stronger an individual identifies as being an athlete, the more likely they are to continue their sports career after an injury. 2) An athlete’s self-worth after an injury significantly impacts their feelings outside athletics. 3) For athletes emotionally impacted by their acute traumatic injury, the injury was a significant factor regarding their athletic performance.